Internally mixed self-repairing concrete densifier
Through the use of internally added self-repair concrete compacting agent, the problems of insufficient anti-seepage performance of existing compacting agents and inability to repair cracks are solved, and the efficient anti-seepage and self-repair effect of concrete is achieved, and its service life is extended.
Patent Information
- Application Number
- CN202510167151.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-15
AI Technical Summary
The existing concrete compacting agent has shortcomings in terms of impermeability resistance and cannot effectively repair concrete cracks, which limits its use in actual engineering applications.
The internally doped self-repair concrete compacting agent is used, which consists of water-soluble polymer, expansion agent, shrinking agent, organic fiber and modifier. The modifiers include bauxite, diatomaceous earth and forsterite powder to achieve crack repair through chemical reactions and osmosis.
It significantly improves the seepage resistance and self-repairing properties of concrete, extends the service life of concrete structures, and enhances the stability of its overall structure.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete densifiers, and in particular to an internally mixed self-repairing concrete densifier. Background Art
[0002] As one of the most widely used building materials, the durability and stability of concrete play a vital role in the long-term safety and performance of buildings. However, during its service, concrete structures will inevitably be affected by various external factors, resulting in internal cracks and other damage, affecting its performance.
[0003] As an important component of concrete, compacting agent plays a key role in the performance of concrete. Compacting agent can improve the internal structure of concrete, make it more dense, reduce porosity and the generation of microcracks, thereby improving the concrete's impermeability, frost resistance and ability to resist chemical erosion. However, existing concrete compacting agents still have many shortcomings in terms of impermeability. Although some compacting agents can improve the density of concrete to a certain extent, they cannot effectively repair concrete cracks, resulting in their limitation in practical engineering applications. Therefore, it is necessary to obtain a concrete compacting agent with excellent impermeability. Summary of the invention
[0004] The present invention provides an internally mixed self-repairing concrete densifier, which solves the problem in the related art that the concrete densifier has poor anti-permeability performance in improving concrete.
[0005] The technical solution of the present invention is as follows:
[0006] The present invention provides an internally mixed self-repairing concrete densifier, which comprises the following components in parts by weight: 10-15 parts of a water-soluble polymer, 12-18 parts of an expansion agent, 1-3 parts of a shrinkage reducer, 2-8 parts of an organic fiber, 10-15 parts of a modifier, and 30-50 parts of a diluent;
[0007] The components of the modifier include bauxite, diatomaceous earth and forsterite powder in a mass ratio of 1:1:8 to 8:1:1.
[0008] As a further technical solution, the expansion agent includes one or more of calcium sulfoaluminate expansion agent, magnesium oxide expansion agent, and calcium oxide expansion agent.
[0009] In the present invention, the expansive agent can react chemically with the components in cement during the cement hydration process to generate expansion products, thereby compensating for the shrinkage of concrete during the hardening process and filling cracks. It is added to concrete as a component of the internal admixture self-repairing concrete densifier, which can extend the service life of the concrete structure; among them, the expansive agent is preferably a magnesium oxide expansive agent or a calcium oxide expansive agent.
[0010] As a further technical solution, the water-soluble polymer includes one or both of polyvinyl alcohol and polyethylene glycol.
[0011] As a further technical solution, the shrinkage reducing agent includes a polyether shrinkage reducing agent.
[0012] Among the components of the internally-added self-repairing concrete densifier of the present invention, the shrinkage reducing agent can be adsorbed on the interface between cement paste and air and water in the concrete mixture, thereby reducing the surface tension of the interface, reducing the shrinkage deformation of the concrete, and extending the service life of the concrete.
[0013] As a further technical solution, the diameter of the organic fiber is 15-30 μm and the length is 0.5-2 mm.
[0014] As a further technical solution, the organic fiber includes one or more of polypropylene fiber, polyacrylonitrile fiber, and polyethylene fiber.
[0015] In the present invention, the organic fiber has high tensile strength and flexibility. When it is evenly dispersed in concrete as a component of the internally added self-repairing concrete densifier, it is interspersed between cement pastes and can withstand part of the stress caused by external forces, prevent the generation and expansion of cracks, and enhance the overall structural stability of the concrete.
[0016] As a further technical solution, the modifier also includes sodium carbonate as a component, and the mass of the sodium carbonate is 6% to 10% of the total mass of the bauxite, diatomaceous earth and forsterite powder.
[0017] As a further technical solution, the preparation method of the modifier includes the following steps: mixing bauxite, diatomaceous earth, forsterite powder and sodium carbonate, and reacting to obtain the modifier.
[0018] In the present invention, sodium carbonate is used to activate and modify bauxite, diatomite and forsterite powder at high temperature to increase the content of active substances in the bauxite, diatomite and forsterite powder. After the prepared internally mixed self-repairing concrete densifier is added to concrete, the anti-permeability, self-repairing performance and durability of the concrete are improved.
[0019] As a further technical solution, the modifier also includes n-octyl phosphoric acid; the mass of n-octyl phosphoric acid is 0.1% to 3% of the total mass of the bauxite, diatomaceous earth and forsterite powder.
[0020] As a further technical solution, the preparation method of the modifier comprises the following steps:
[0021] S1, mixing bauxite, diatomite, forsterite powder and sodium carbonate, reacting to obtain a reactant;
[0022] S2. Mixing the reactant and n-octyl phosphoric acid to obtain a modifier.
[0023] As a further technical solution, the reaction temperature is 800-820°C and the reaction time is 1.5-2h.
[0024] In the present invention, bauxite, diatomite and forsterite powder are activated and modified by sodium carbonate at high temperature, and then modified by n-octyl phosphoric acid to prevent the bauxite, diatomite and forsterite powder from settling. After the prepared internally mixed self-repairing concrete densifier is added to concrete, the impermeability and durability of the concrete are improved.
[0025] The present invention also provides a method for preparing the internally mixed self-repairing concrete densifier, comprising the following steps:
[0026] The components of the internally mixed self-repairing concrete densifier are mixed and dried to obtain the internally mixed self-repairing concrete densifier.
[0027] The working principle and beneficial effects of the present invention are:
[0028] In the present invention, the components of the internally mixed self-repairing concrete densifier are compounded with bauxite, diatomite and forsterite powder, and are combined with water-soluble polymers, expansion agents, shrinkage reducers, organic fibers and other components. The water-soluble polymer can form a continuous polymer film inside the concrete, so that the connection between cement particles is tighter, and the concrete pores are effectively filled; the expansion agent undergoes a chemical reaction during the concrete hardening process to produce moderate expansion, and the shrinkage reducer can reduce the surface tension of the concrete pore fluid. During the concrete drying process, the capillary shrinkage stress caused by water evaporation can be effectively reduced, and the shrinkage of the concrete caused by cement hydration reaction can be effectively compensated, and the shrinkage stress inside the concrete can be reduced; finally, after the internally mixed self-repairing concrete densifier is added to the concrete, the anti-permeability performance of the concrete is significantly improved, and the durability is also improved;
[0029] At the same time, after cracks appear in the concrete, although the concrete itself can use water to further hydrate the incompletely hydrated parts and achieve a certain self-repairing effect, the degree of self-repairing of the concrete itself is limited. The internally added self-repairing concrete densifier prepared by the present invention is added to the concrete. When cracks appear in the concrete, the active substances, water-soluble polymers and other components in the modifier use osmosis to penetrate into the cracks with water, and complex and precipitate with calcium hydroxide, free calcium ions, etc. to form crystals to repair the cracks, thereby improving the self-repairing performance of the concrete. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the following examples and comparative examples, magnesium oxide expansion agent and calcium oxide expansion agent were purchased from Beijing Dechang Weiye Construction Engineering Technology Co., Ltd.;
[0032] The particle size of diatomaceous earth is 325 mesh, and the silica content is 88wt%;
[0033] The particle size of forsterite powder is 300 mesh, the magnesium oxide content is 57wt%, and the silicon dioxide content is 43wt%;
[0034] The particle size of bauxite is 325 mesh, the aluminum oxide content is 70wt%, and the silicon dioxide content is 10wt%.
[0035] Example 1
[0036] The internally mixed self-repairing concrete densifier comprises the following components in parts by weight: 12 parts of polyvinyl alcohol (model PVA1788), 5 parts of magnesium oxide expansion agent, 10 parts of calcium oxide expansion agent, 2 parts of dodecyl alcohol polyoxyethylene ether, 6 parts of polypropylene fiber (diameter 15 μm, length 0.5 mm), 12 parts of modifier, and 40 parts of water;
[0037] The modifier comprises bauxite, diatomite and forsterite powder in a mass ratio of 1:1:3;
[0038] The preparation method of the modifier comprises the following steps: mixing bauxite, diatomite and forsterite powder at room temperature for 1.5 hours to obtain the modifier;
[0039] The preparation method of the internally mixed self-repairing concrete densifier comprises the following steps:
[0040] The components of the internally mixed self-repairing concrete densifier are stirred and mixed, and then dried to obtain the internally mixed self-repairing concrete densifier.
[0041] Example 2
[0042] The internally mixed self-repairing concrete densifier comprises the following components in parts by weight: 10 parts of polyvinyl alcohol (model PVA1788), 12 parts of magnesium oxide expansion agent, 1 part of dodecyl alcohol polyoxyethylene ether, 1 part of polypropylene fiber (diameter 30 μm, length 1 mm), 1 part of polyacrylonitrile fiber (diameter 15 μm, length 0.5 mm), 10 parts of modifier, and 30 parts of water;
[0043] The modifier comprises bauxite, diatomite and forsterite powder in a mass ratio of 1:1:8;
[0044] The preparation method of the modifier comprises the following steps: mixing bauxite, diatomite and forsterite powder at room temperature for 1.5 hours to obtain the modifier;
[0045] The preparation method of the internally mixed self-repairing concrete densifier comprises the following steps:
[0046] The components of the internally mixed self-repairing concrete densifier are stirred and mixed, and then dried to obtain the internally mixed self-repairing concrete densifier.
[0047] Example 3
[0048] The internally mixed self-repairing concrete densifier comprises the following components in parts by weight: 15 parts of polyvinyl alcohol (model PVA1788), 18 parts of calcium oxide expansion agent, 3 parts of dodecyl alcohol polyoxyethylene ether, 8 parts of polypropylene fiber (diameter of 15 μm, length of 2 mm), 15 parts of modifier, and 50 parts of water;
[0049] The modifier comprises bauxite, diatomite and forsterite powder in a mass ratio of 8:1:1;
[0050] The preparation method of the modifier comprises the following steps: mixing bauxite, diatomite and forsterite powder at room temperature for 1.5 hours to obtain the modifier;
[0051] The preparation method of the internally mixed self-repairing concrete densifier comprises the following steps:
[0052] The components of the internally mixed self-repairing concrete densifier are stirred and mixed, and then dried to obtain the internally mixed self-repairing concrete densifier.
[0053] Example 4
[0054] The only difference between this embodiment and embodiment 1 is that the preparation method of the modifier includes the following steps: mixing bauxite, diatomaceous earth and forsterite powder at 820° C. for 1.5 hours to obtain the modifier.
[0055] Example 5
[0056] The only difference between this embodiment and embodiment 1 is that the preparation method of the modifier includes the following steps: mixing bauxite, diatomite, forsterite powder and sodium carbonate at 820° C. for 1.5 hours to obtain a modifier; wherein the mass of sodium carbonate is 6% of the total mass of bauxite, diatomite and forsterite powder.
[0057] Example 6
[0058] The only difference between this embodiment and embodiment 1 is that the preparation method of the modifier includes the following steps: mixing bauxite, diatomite, forsterite powder and sodium carbonate at 800° C. for 2 hours to obtain a modifier; wherein the mass of sodium carbonate is 10% of the total mass of bauxite, diatomite and forsterite powder.
[0059] Example 7
[0060] The difference between this embodiment and embodiment 6 is that the preparation method of the modifier comprises the following steps:
[0061] S1, mixing bauxite, diatomite, forsterite powder and sodium carbonate for reaction at 800° C. for 2 h to obtain a reactant;
[0062] S2, mixing the reactant and n-octyl phosphoric acid at 100° C. to obtain a modifier;
[0063] The mass of sodium carbonate is 10% of the total mass of bauxite, diatomaceous earth and forsterite powder; the mass of n-octyl phosphoric acid is 3% of the total mass of bauxite, diatomaceous earth and forsterite powder.
[0064] Example 8
[0065] The difference between this embodiment and embodiment 6 is that the preparation method of the modifier comprises the following steps:
[0066] S1, mixing bauxite, diatomite, forsterite powder and sodium carbonate for reaction at 820° C. for 1.5 h to obtain a reactant;
[0067] S2, mixing the reactant and n-octyl phosphoric acid at 100° C. to obtain a modifier;
[0068] The mass of sodium carbonate is 6% of the total mass of bauxite, diatomaceous earth and forsterite powder; the mass of n-octyl phosphoric acid is 0.1% of the total mass of bauxite, diatomaceous earth and forsterite powder.
[0069] Comparative Example 1
[0070] The difference between this comparative example and Example 1 is that the components of the modifier include bauxite and diatomaceous earth in a mass ratio of 1:1;
[0071] The preparation method of the modifier comprises the following steps: mixing bauxite and diatomaceous earth at room temperature for 1.5 hours to obtain the modifier.
[0072] Comparative Example 2
[0073] The difference between this comparative example and Example 1 is that the components of the modifier include diatomaceous earth and forsterite powder in a mass ratio of 1:3;
[0074] The preparation method of the modifier comprises the following steps: diatomite and forsterite powder are mixed at room temperature for 1.5 hours to obtain the modifier.
[0075] Comparative Example 3
[0076] The difference between this comparative example and Example 1 is that the components of the modifier include bauxite and forsterite powder in a mass ratio of 1:3;
[0077] The preparation method of the modifier comprises the following steps: mixing bauxite and forsterite powder at room temperature for 1.5 hours to obtain the modifier.
[0078] Experimental Example 1
[0079] After mixing the internally mixed self-repairing concrete densifiers prepared in Examples 1 to 8 and Comparative Examples 1 to 3 with silicate cement and quartz sand to prepare concrete (the mass ratio of the internally mixed self-repairing concrete densifier, silicate cement and quartz sand is 25:50:35), the anti-seepage pressure ratio test was carried out with reference to GB 18445-2012 "Cement-based permeable crystalline waterproof material" and T / CECS 913-2021 "Standard for Test Method for Self-repairing Performance of Cement Concrete", and the results are shown in Table 1.
[0080] Table 1 Performance test results
[0081]
[0082] Compared with Comparative Examples 1 to 3, the 28d impermeability pressure ratio of the concrete made of the internally mixed self-repairing concrete densifier and cement and other components prepared in Examples 1 to 8 reached more than 400%. It can be seen that bauxite, diatomaceous earth and forsterite powder are compounded, and bauxite, diatomaceous earth and forsterite powder are activated and modified with sodium carbonate and n-octyl phosphoric acid to obtain the internally mixed self-repairing concrete densifier, which is added to the concrete to improve the impermeability of the concrete.
[0083] Experimental Example 2
[0084] After mixing the internally mixed self-repairing concrete densifiers prepared in Examples 1 to 6 and Comparative Examples 1 to 3 with silicate cement and quartz sand to prepare concrete (the mass ratio of the internally mixed self-repairing concrete densifier, silicate cement and quartz sand is 25:50:35), refer to GB 18445-2012 "Cement-based permeable crystalline waterproof material" and T / CECS 913-2021 "Standard for Test Method for Self-repairing Performance of Cement Concrete", and calculate the anti-seepage pressure recovery rate of concrete water pressure damage after self-repair according to the anti-seepage pressure ratio measured in Experimental Example 1, and the results are shown in Table 2.
[0085] Table 2 Performance test results
[0086]
[0087] Compared with Comparative Examples 1 to 3, the anti-seepage pressure recovery rate of concrete made of the internally mixed self-repairing concrete densifier and cement and other components prepared in Examples 1 to 6 reached more than 86%, thereby improving the self-repairing performance of the concrete.
[0088] Experimental Example 3
[0089] After the internally added self-repairing concrete densifiers prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were mixed with Portland cement and quartz sand to prepare concrete (the mass ratio of the internally added self-repairing concrete densifier, Portland cement and quartz sand was 25:50:35), the corrosion resistance coefficient was tested with reference to GB / T 749-2008 "Test method for resistance of cement to sulfate attack", and the results are shown in Table 3.
[0090] Table 3 Performance test results
[0091]
[0092] Compared with Comparative Examples 1 to 3, the corrosion resistance coefficient of the concrete made from the internally-added self-repairing concrete densifier and cement and other components prepared in Examples 1 to 8 reached above 0.93K. It can be seen that the components of the internally-added self-repairing concrete densifier contain bauxite, diatomaceous earth and forsterite powder, and are activated and modified with sodium carbonate, which improves the durability of the concrete.
[0093] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. Internally mixed self-repairing concrete densifier, characterized in that: The invention comprises the following components in parts by weight: 10-15 parts of water-soluble polymer, 12-18 parts of swelling agent, 1-3 parts of shrinkage reducing agent, 2-8 parts of organic fiber, 10-15 parts of modifier, and 30-50 parts of diluent; The components of the modifier include bauxite, diatomaceous earth and forsterite powder in a mass ratio of 1:1:8 to 8:1:
1.
2. The internally mixed self-repairing concrete densifier according to claim 1, characterized in that: The expansion agent includes one or more of calcium sulfoaluminate expansion agent, magnesium oxide expansion agent and calcium oxide expansion agent.
3. The internally mixed self-repairing concrete densifier according to claim 1, characterized in that: The shrinkage reducing agent includes a polyether shrinkage reducing agent.
4. The internally mixed self-repairing concrete densifier according to claim 1, characterized in that: The organic fiber has a diameter of 15-30 μm and a length of 0.5-2 mm.
5. The internally mixed self-repairing concrete densifier according to claim 1, characterized in that: The organic fiber includes one or more of polypropylene fiber, polyacrylonitrile fiber and polyethylene fiber.
6. The internally mixed self-repairing concrete densifier according to claim 1, characterized in that: The modifier also includes sodium carbonate, and the mass of the sodium carbonate is 6% to 10% of the total mass of the bauxite, diatomaceous earth and forsterite powder.
7. The internally mixed self-repairing concrete densifier according to claim 6, characterized in that: The preparation method of the modifier comprises the following steps: mixing bauxite, diatomite, forsterite powder and sodium carbonate, and reacting to obtain the modifier.
8. The internally mixed self-repairing concrete densifier according to claim 7, characterized in that: The modifier also includes n-octyl phosphoric acid; the mass of the n-octyl phosphoric acid is 0.1% to 3% of the total mass of the bauxite, diatomaceous earth and forsterite powder.
9. The internally mixed self-repairing concrete densifier according to claim 8, characterized in that: The preparation method of the modifier comprises the following steps: S1, mixing bauxite, diatomite, forsterite powder and sodium carbonate, reacting to obtain a reactant; S2. Mixing the reactant and n-octyl phosphoric acid to obtain a modifier.
10. The internally mixed self-repairing concrete densifier according to claim 7 or claim 9, characterized in that: The reaction temperature is 800-820° C. and the reaction time is 1.5-2 hours.
Citation Information
Patent Citations
Flame-retardant fireproof coating
CN104177875A
Composite anti-cracking agent for super-long mass concrete and preparation method of composite anti-cracking agent
CN113213807A